Costamere remodeling with muscle loading and unloading in healthy young men. Issue 5 (8th September 2013) - Li, Ruowei; Narici, Marco V.; Erskine, Robert M.; Seynnes, Olivier R.; Rittweger, Jörn; Pišot, Rado; Šimunič, Boštjan; Flück, Martin
Abstract Costameres are mechano‐sensory sites of focal adhesion in the sarcolemma that provide a structural anchor for myofibrils. Their turnover is regulated by integrin‐associated focal adhesion kinase (FAK). We hypothesized that changes in content of costamere components (beta 1 integrin, FAK, meta‐vinculin, gamma‐vinculin) with increased and reduced loading of human anti‐gravity muscle would: (i) relate to changes in muscle size and molecular parameters of muscle size regulation [p70S6K, myosin heavy chain (MHC)1 and MHCIIA]; (ii) correspond to adjustments in activity and expression of FAK, and its negative regulator, FRNK; and (iii) reflect the temporal response to reduced and increased loading. Unloading induced a progressive decline in thickness of human vastus lateralis muscle after 8 and 34 days of bedrest (−4% and −14%, respectively; n = 9), contrasting the increase in muscle thickness after 10 and 27 days of resistance training (+5% and +13%; n = 6). Changes in muscle thickness were correlated with changes in cross‐sectional area of type I muscle fibers (r = 0.66) and beta 1 integrin content (r = 0.76) at the mid‐point of altered loading. Changes in meta‐vinculin and FAK‐pY397 content were correlated (r = 0.85) and differed, together with the changes of beta 1 integrin, MHCI, MHCII and p70S6K, between the mid‐ and end‐point of resistance training. By contrast, costamere protein level changes did not differ between time points of bedrest. The findings emphasize the role of FAK‐regulated costamere turnover in the load‐dependent addition and removal of myofibrils, and argue for two phases of muscle remodeling with resistance training, which do not manifest at the macroscopic level.